Probing of Three-Dimensional Spin Textures in Multilayers by Field Dependent X-Ray Resonant Magnetic Scattering - Burgos-Parra, E (Nature Research, 2023)
In multilayers of magnetic thin films with perpendicular anisotropy, domain walls can take on hybrid configurations in the vertical direction which minimize the domain wall energy, with Néel walls in the top or bottom layers and Bloch walls in some central layers. These types of textures are theoretically predicted, but their observation has remained challenging until recently, with only a few techniques capable of realizing a three dimensional characterization of their magnetization distribution. Here we perform a field dependent X-ray resonant magnetic scattering measurements on magnetic multilayers exploiting circular dichroism contrast to investigate such structures. Using a combination of micromagnetic and X-ray resonant magnetic scattering simulations along with our experimental results, we characterize the three-dimensional magnetic texture of domain walls, notably the thickness resolved characterization of the size and position of the Bloch part in hybrid walls. We also take a step in advancing the resonant scattering methodology by using measurements performed off the multilayer Bragg angle in order to calibrate the effective absorption of the X-rays, and permitting a quantitative evaluation of the out of plane (z) structure of our samples. Beyond hybrid domain walls, this approach can be used to characterize other periodic chiral structures such as skyrmions, antiskyrmions or even magnetic bobbers or hopfions, in both static and dynamic experiments. © 2023, The Author(s).